Herodotus in Nubia - Török, László, 1941- (Mnemosyne, Supplements, 2014)
Twentieth century commentaries on Herodotus' passages on Nubia, the historical kingdom of Kush and the Aithiopia of the Greek tradition, rely mostly on an outdated and biased interpretation of the textual and archaeological evidence. Disputing both the Nubia image of twentieth century Egyptology and the Herodotus interpretation of traditional Quellenkritik , the author traces back the Aithiopian information that was available to Herodotus to a discourse on Kushite kingship created under the Nubian pharaohs of the Twenty-Fifth Dynasty and preserved in the Ptah sanctuary at Memphis. Insufficient for a self-contained Aithiopian logos, the information acquired by Herodotus complements and supports accounts of the land, origins, customs and history of other peoples and bears a relation to the intention of the actual narrative contexts into which the author of The Histories inserted it.